Characterization of the concrete alkali reactivity of granitoid and dolomitic aggregates - Sabino, N. (2010)
The general designation of “internal expansive reactions” includes the alkali-silica reaction (ASR) and the internal sulfate attack by delayed ettringite formation (DEF). These reactions are characterized by the formation of expansive compounds in hardened concrete and consequent cracking of the structure. In Portugal, the number of structures, mainly dams and bridges, affected by ASR is very significant and in some cases require considerable investment in rehabilitation interventions. Moreover, previous research has shown that the use of some aggregates, initially regarded as inert, can cause problems, proving the need for further insight on the role of aggregates and prevent the occurrence of ASR in constructions. The economic value of various types of structures (e.g. dams, bridges, airfields) and the high costs related to structural degradation including losses of functionality and the permanent or temporary unavailability (for repair and rehabilitation) could be an important overthrow. Thus thorough understanding of the earth materials requirements for concrete manufacture are of vital economic importance in view of the prevention of deterioration and aging of structures whose longevity and functionality must be guaranteed. It is imperative to provide the concrete producers with the necessary knowledge in order to avoid this type of concrete degradation. Particularly important is the recently approved Lisbon-Madrid High Speed Train railway construction. This expensive operation will require large quantities of aggregates for the construction of bridges and other concrete infrastructures. Three main sources of raw materials will be considered for the study: St. Eulalia, Montemor and Cano. These quarries are already major exploitation sites separated by 50 km and not far from the future High Speed Train railway. Two of them are granitoid rocks but the raw material from St. Eulalia is richer in quartz and poorer in ferromagnesian minerals than the Montemor aggregates. The enrichment in calcium of feldspar goes together with the iron and the magnesium. The Cano aggregates are very different materials. The main lithology is a dolomite rock with local microscopic enrichments in phyllosilicates and very deformed quartz. Mineralogical and textural characterization of the aggregates was done by optical microscopy. The crystallinity of quartz was also evaluated by XRD and FTIR. The aggregates were also studied by accelerated expansion mortar-bar and concrete-prism tests to evaluate their potentially alkali-reactivity. The relationship between aggregates characteristics and their behaviour in what concerns to alkali reactivity will be discussed.